Short Communication: Bacterial diversity of mangrove ecosystem in Klawalu Sorong, West Papua, Indonesia - SUKMAWATI SUKMAWATI; FEBRIANTI ROSALINA; SIPRIYADI SIPRIYADI; NURUL KUSUMA DEWI; MELDA YUNITA; ABDUL RIDHA TAHA SARHAN; YENI RAHAYU; EKO KUSUMAWATI (Society for Indonesian Biodiversity, 2022)
Abstract. Sukmawati S, Rosalina F, Sipriyadi, Dewi NK, Yunita M, Sarhan ART, Rahayu Y, Kusumawati E. 2022. Short Communication: Bacterial diversity of mangrove ecosystem in Klawalu Sorong, West Papua, Indonesia. Biodiversitas 23: 1427-1432. The mangrove ecosystem is a producer of detritus and a source of nutrients and organic matter. Some of the ecological functions of mangrove forests are coastline protector, preventing seawater intrusion, as a habitat for various living creatures, a microclimate regulator, a nursery ground, spawning ground, as well as a feeding ground for various aquatic biota. The mangrove forest ecosystem cannot be separated from the role of microbes in helping the process of soil biochemical cycles. In the biochemical cycle, microbes are able to maintain the availability of macronutrients in the soil. The objective of this study was to identify the diversity of bacteria in the mangrove ecosystem in Klawalu, Sorong City. The research method descriptively described the diversity of bacterial species found in the mangrove ecosystem in Klawalu, Sorong City, West Papua Province. The results indicated that the DNA fragments of the four isolates obtained from this study were around 1300 bp. Meanwhile, the bacterial species obtained were isolated SA3, identified as Bacillus safensis strain C251, isolate SA8 identified as Bacillus amyloliquefaciens strain NO10, isolate SL8 was identified as Clostridium sp. JC336, and isolate SL1 was identified as Bacillus australimaris strain IIHR GAPB01.